1988
DOI: 10.1530/acta.0.1190459
|View full text |Cite
|
Sign up to set email alerts
|

Evening urinary free corticoids: a screening test in Cushing's syndrome and incidentally discovered adrenal tumours

Abstract: In this study, we investigated the usefulness of the determination of evening urinary free corticoids/ creatinine in samples collected from 20.00 to 24.00 h as a screening test in Cushing's syndrome. In controls (N = 61) the ratio values ranged from 1.1 to 9.4 \g=m\mol/mol,whereas in patients with Cushing's syndrome (N = 20), they ranged from 27.5 to 855.5 \g=m\mol/mol. However, in 28% of patients with major obesity (> 50% overweight) and no hypercortisolism, the ratio values were between 9.4 to 27.8 \g=m\mol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…We suggest that a screening procedure for Cushing's syndrome could combine this simple and stress-tree test with the measurement of evening urinary cortisol level (19), because both saliva and evening urine collections can be obtained easily in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that a screening procedure for Cushing's syndrome could combine this simple and stress-tree test with the measurement of evening urinary cortisol level (19), because both saliva and evening urine collections can be obtained easily in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Copeland [23] sug gested in 1983 that prevalence of adrenocortical tumors appearing to have no secretory activity decreases as indices of steroid metabolism are more closely scruti nized. Also, Laudat et al [24] reported the utility of a timed 4-hour collection for UFC and creatinine between 8 p.m. and midnight compared with the 24-hour UFC in 10 patients with incidentaloma previously described as 'hormonally normal'. All 61 control patients had an eve ning UFC/Cr ratio less than lOpmol/mol, while 8/10 patients with incidentalomas had an evening UFC/Cr ratio greater than 10 pmol/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the possibility of diagnosing Cushing's syndrome by collecting urine for less than 24 h (Contreras et al, 1986;Laudat et al, 1988). However, the urine sampling is frequently inaccurate.…”
mentioning
confidence: 99%